Red phosphor based on Eu3+-isoelectronically doped Ba2SiO4 obtained via sol-gel route for solid state lightning - Bispo, Airton G. [UNESP]; Ceccato, Diego A. [UNESP]; Lima, Sergio A.M. [UNESP]; Pires, Ana M. [UNESP] (Royal Society of Chemistry (RSC), 2017)
The present paper reports on the effect of Eu3+ concentration (1-5%, considering a charge compensation mechanism) on the structural, morphological and spectroscopic properties of Ba2SiO4 produced by using a novel approach that involves an adapted sol-gel route. XRD data showed that high crystalline and single phase doped Ba2SiO4 samples were prepared at lower calcination temperature (1100 °C) compared to the standard solid-state method (∼1300 °C). FTIR, Raman and DRS analyses indicated that the Ba2+ replacement by Eu3+ ions causes punctual structural defects in the Ba2SiO4 lattice, which particles observed by SEM imaging have irregular shape characteristics for the use of the acid-catalyzed sol-gel method. Optical bandgap values evaluated by DRS measurements of the red phosphors are smaller (∼4.5 eV) than that of the nominally pure matrix (∼5.8 eV), evidencing that Eu3+ ions increase Ba2SiO4 structural/electronic defects. The detailed analysis of the f-f Eu3+ narrow transitions in the photoluminescence spectra showed that doping ions occupy at least two non-equivalent sites without an inversion center in the Ba2SiO4 host. Moreover, the 5% doped sample also exhibited a third Eu3+ anomalous site assigned to the Eu3+-O2- associates, which has a spectral behavior distinct from Eu3+ occupying ordinary host lattice sites. Finally, the 4%-doped sample exhibited the highest relative emission intensity while the 5%-doped, the highest quantum efficiency (72.6%) which qualifies these materials as potential candidates to be used as red phosphors for solid state lightning.